Novel perovskite composite material and band gap regulation and control method thereof

Through the combination of new perovskite composite materials and two-dimensional MXene and band gap regulation methods, the stability and band gap adaptation problems of traditional perovskite materials are solved, and the research and development of non-toxic and harmless photoelectric materials is realized, and the new materials are simplified. The R&D process and reduce costs.

CN119320179AActive Publication Date: 2025-01-17DALIAN UNIV OF TECH +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411878094.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-01-17
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

Traditional all-inorganic perovskite materials have stability problems and contain harmful lead elements, which limits their development in commercial applications, and the prior art is difficult to quickly and efficiently regulate their band gaps to meet the needs of photoelectric materials.

Method used

New perovskite composite materials, including ABX3 all-inorganic perovskite and two-dimensional MXene, are used to adjust the doping ratio of two-dimensional MXene to regulate the band gap, and build a stable perovskite composite material, and use Materials Studio software to model it Construction and bandgap calculations were used to optimize heterostructures to obtain materials with bandgaps around 1.5 eV.

Benefits of technology

It realizes a non-toxic and harmless perovskite composite material, simplifies the band gap regulation process, reduces the complexity and cost of new materials research and development, shortens the R&D cycle, and has important practical application value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320179A_ABST
    Figure CN119320179A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of design and development of photoelectric materials, in particular to a novel perovskite composite material and a band gap regulation and control method thereof.The material comprises ABX3 type all-inorganic perovskite and two-dimensional MXene with the molar ratio being (1-50): 1; in the ABX3 type all-inorganic perovskite, the A site is replaced by Cs, the B site is replaced by Pt, and the X site is replaced by a halogen element; the two-dimensional MXene is transition metal carbide, nitride or boride, the material is non-toxic and harmless, and the band gap of the material is adaptive to that of a photoelectric material; the material band gap regulation and control method comprises the following steps: selecting an initial material, constructing a theoretical model and a composite material, optimizing a structure, calculating composite energy, selecting a theoretical model with a stable structure, and analyzing a result after band gap calculation. According to the CsPtX3 / MXene composite material, the size of the band gap is regulated and controlled by changing the doping ratio of the two-dimensional MXene, and the structure and composition of the CsPtX3 / MXene composite material which is stable in structure and has the band gap of about 1.5 eV are obtained, so that the operation complexity of finding a proper band gap material in an experiment is reduced, the research and development period of a new material is shortened, the cost is saved, and the CsPtX3 / MXene composite material has important practical application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of design and development of optoelectronic materials, and in particular to a novel perovskite composite material and a band gap control method thereof. Background Art

[0002] All-inorganic perovskite materials (CsPbX 3 , X = Cl, Br, I) have become the best optoelectronic materials with their excellent optoelectronic properties, such as high quantum efficiency and narrow half-width, and are used in backlight display, solar cells, LED lighting and other fields; however, their stability issues have seriously limited their development in commercial applications. 3 It contains lead, which is harmful to the human body and causes certain pollution to the environment.

[0003] In perovskite ABX 3 In the research, doping and surface engineering are the methods to improve the perovskite ABX 3 MXene material is a new type of two-dimensional transition metal carbide or carbonitride, which is obtained by selectively etching the A layer in the MAX phase material. The general chemical formula of MXene is M n+1 X n T x Where M represents transition metal (Ti, V, Cr, Mo, etc.), X represents carbon or nitrogen, n = 1-3, T x Represents surface functional groups, such as F, O, and OH. MXene materials have excellent thermal stability, conductivity, hydrophilicity, and mechanical properties, as well as high specific surface area and interlayer ion storage capacity, making them very promising 2D materials that can be used in solar cells, photocatalysis, and other fields.

[0004] Developing a new type of stable, harmless material that can be used in the optoelectronic field has very important practical value. Summary of the invention

[0005] The purpose of the present invention is to provide a new type of perovskite composite material and a method for regulating its band gap, wherein the new type of perovskite composite material is non-toxic and harmless compared to traditional all-inorganic perovskites, and the band gap is suitable for the application of optoelectronic materials; the band gap regulation method of the new type of perovskite composite material can efficiently and quickly regulate the size of the band gap by changing the doping ratio of the two-dimensional MXene material, and obtain a structurally stable perovskite composite material composition.

[0006] To achieve the above object, the present invention adopts the following technical solutions: A novel perovskite composite material, comprising: ABX 3Type all-inorganic perovskite and two-dimensional MXene; The ABX 3 The molar ratio of all-inorganic perovskite and two-dimensional MXene is (1~50):1; The ABX 3 In the all-inorganic perovskite, the element replacing the A position is Cs, the transition element replacing the B position is Pt, and the element replacing the X position is a halogen element; The two-dimensional MXene is a transition metal carbide, nitride or boride.

[0007] Preferably, the halogen elements include Cl, Br, and I, and the element replacing the X position is any combination of one or more of Cl, Br, and I.

[0008] Preferably, the carbide is M 2 C.M. 3 C 2 、M 4 C 3 One of them; the nitride includes M 2 N, M 3 N 2 and M 4 N 3 One of the following; the boride comprises M 2 B 2 、M 3 B 4 and M 4 B 6 One of them.

[0009] A band gap control method for a novel perovskite composite material comprises the following steps: S1: Using the Materials Studio software package, the uncomplexed CsPtX 3 Band gap calculations for selected conductive 2D MXenes and CsPtX 3 construct composite materials; S2: CsPtX 3 Perovskite and 2D MXene are modeled in molar proportions using Materials Studio to construct CsPtX 3 / MXene theoretical model; S3: Based on the theoretical model of S2, construct CsPtX 3 / MXene composites; S4: Based on S2, a theoretical model was established and the heterostructure was optimized using Materials Studio to calculate the CsPtX 3 / MXene composite binding energy; S5: Select stable CsPtX according to constraints 3 / MXene heterogeneous model and the corresponding CsPtX 3 / MXene composites; S6: According to the CsPtX in S5 3 / MXene composite materials, band gap calculation was performed using Materials Studio, and (GGA-PBE)-HSE03-HSE06 were performed in sequence to obtain the band gap calculation results; S7: Analyze the band gap calculation results and obtain CsPtX 3 Material structure and composition of / MXene composite materials with a band gap of 1.5 eV.

[0010] Preferably, in S3, CsPtX 3 When the molar ratio of perovskite and two-dimensional MXene is (50~21):1, the two-dimensional MXene is used as the core of the composite material, and CsPtX 3 Perovskite is coated on the surface of two-dimensional MXene to construct a composite material; CxP 3 When the molar ratio of perovskite and two-dimensional MXene is (20~1):1, the composite material is constructed in the form of a laminated sandwich structure. 3 Perovskite-2D MXene-CsPtX 3 Modeling of the three-layer sandwich structure of perovskite.

[0011] Preferably, the CsPtX in S4 3 The binding energy of the / MXene composite material is E binding = E CsPtX3 / MXene - E CsPtX3 - E MXene ;in, E CsPtX3 / MXene is the total energy of the composite material, E CsPtX3 For CsPtX 3 The total energy of the perovskite, E MXene is the total energy of the two-dimensional MXene.

[0012] Preferably, the constraint condition is CsPtX 3 / MXene composite material binding energy is less than 0.

[0013] Preferably, in S2, the corresponding CsPtX is constructed according to different molar ratio gradients. 3 Theoretical models of perovskite and two-dimensional MXene, repeat S3~S7 for each of the theoretical models.

[0014] Compared with the prior art, the present invention has the following beneficial effects: Compared with the traditional all-inorganic perovskite, the new perovskite composite material provided in the above technical solution is non-toxic and harmless, and the band gap is suitable for the application of optoelectronic materials; the band gap regulation method of the new perovskite composite material can efficiently and quickly regulate the size of the band gap by changing the doping ratio of the two-dimensional MXene material, and obtain a stable structure and a band gap of about 1.5eV CsPtX 3 / MXene composite materials, thereby reducing the complexity of experimental operations to find suitable band gap materials, shortening the research and development cycle of new materials and saving costs, which has important practical application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 The perovskite material CsPtCl provided in the embodiment of the present invention 3 Schematic diagram of the theoretical model.

[0016] Figure 2 The two-dimensional MXene Ti provided in the embodiment of the present invention 3 C 2 Schematic diagram of the theoretical model.

[0017] Figure 3 The perovskite material CsPtCl provided in the embodiment of the present invention 3 Schematic diagram of the band gap.

[0018] Figure 4 It is CsPtCl provided in the embodiment of the present invention 3 / Ti 3 C 2 Schematic diagram of the band gap of the composite material. DETAILED DESCRIPTION

[0019] The invention will be described in more detail below in conjunction with the accompanying drawings. It should be noted that the description of the invention with reference to the accompanying drawings is only illustrative and not restrictive. The various embodiments can be combined with each other to form other embodiments not shown in the following description.

[0020] The novel perovskite composite material of the present invention comprises ABX 3 Type all-inorganic perovskite and two-dimensional MXene; among them, ABX 3In the all-inorganic perovskite, the element replacing the A position is Cs, the transition element replacing the B position is Pt, the element replacing the X position is a halogen element, the halogen element includes Cl, Br, I, and the element replacing the X position is any combination of Cl, Br, I or more thereof; for example, CsPtCl 3 , CsPtBr 3 ,CsPtI 3 , CsPtCl 2 Br, CsPtCl 2 I、CsPtClBrI、CsPtClBr 2 , CsPtClI 2 wait; Two-dimensional MXenes are transition metal carbides, nitrides or borides, including M 2 C.M. 3 C 2 、M 4 C 3 、M 2 N, M 3 N 2 、M 4 N 3 、M 2 B 2 、M 3 B 4 and M 4 B 6 Etc., specifically Ti 2 C. Ti 2 N.V. 2 C、Nb 2 C. Ti 3 C 2 、Ti 3 CN、Nb 4 C 3 、 4 C 3 、Ti 4 N 3 、Mo 2 Ti 2 C 3 Potential structures such as 2D materials and possible 2D materials with multiple single (-O, -Cl, -F, etc.) or mixed (O / OH / F) surface terminal groups; Compared with traditional all-inorganic perovskite, the new perovskite composite material is non-toxic and harmless, and its band gap is suitable for the application of optoelectronic materials.

[0021] The band gap control method of the novel perovskite composite material of the present invention comprises the following steps: (1) Initial material selection; Using the Materials Studio software package, the uncomplexed CsPtX 3 Band gap calculation, select CsPtX with a band gap greater than 1.5 eV or a band gap less than 1.5 eV 3 Perovskite; select a two-dimensional MXene with conductivity, preferably a two-dimensional MXene with good conductivity.

[0022] (2) Constructing a theoretical model CsPtX 3 Perovskite and 2D MXene are modeled in molar proportions using Materials Studio to construct CsPtX 3 / MXene theoretical model, CsPtX 3 The molar ratio of perovskite and two-dimensional MXene is (1~50):1.

[0023] (3) Construction of composite materials According to the theoretical model of step (2), CsPtX 3 / MXene composites; CxP 3 When the molar ratio of perovskite and two-dimensional MXene is (50~21):1, the two-dimensional MXene is used as the core of the composite material, and CsPtX 3 Perovskite is coated on the surface of two-dimensional MXene to construct a composite material; CxP 3 When the molar ratio of perovskite and two-dimensional MXene is (20~1):1, the composite material is constructed in the form of a laminated sandwich structure. 3 Perovskite-2D MXene-CsPtX 3 Modeling of the three-layer sandwich structure of perovskite.

[0024] (4) Optimize structure and calculate composite energy Based on the theoretical model, the heterostructure was optimized using Materials Studio to calculate the CsPtX 3 / MXene composite binding energy; CsPtX 3 The binding energy of the / MXene composite material is E binding = E CsPtX3 / MXene - E CsPtX3 - E MXene ;in, E CsPtX3 / MXene is the total energy of the composite material, ECsPtX3 For CsPtX 3 The total energy of the perovskite, E MXene is the total energy of the two-dimensional MXene.

[0025] (5) Selecting a theoretical model for structural stability According to the constraints: CsPtX 3 When the binding energy of the / MXene composite material is less than 0, a structurally stable heterogeneous model is selected, and the CsPtX 3 / MXene composites.

[0026] (6) Band gap calculation The band gap calculation was performed using Materials Studio, with (GGA-PBE)-HSE03-HSE06 as the progressive step-by-step band gap calculation. During the calculation process, the low-precision method was used for preliminary optimization, and the accuracy was further improved on the basis of obtaining a stable structural model. This is an appropriate method that can significantly improve the calculation efficiency and reduce the calculation workload, and helps to quickly obtain the band gap calculation results.

[0027] (7) Analysis of band gap calculation results According to the band gap calculation results obtained in step (6), CsPtX with a band gap of about 1.5 eV is selected. 3 / MXene composites and obtain CsPtX 3 Structure and composition of / MXene composites.

[0028] Below is CsPtX 3 Taking / MXene composite material as an example, the method of the present invention is described in detail.

[0029] In this embodiment, the halogen element selected to replace the X position is Cl, that is, CsPtCl 3 Perovskite; In terms of the selection of two-dimensional MXene, the conductivity of carbides is better than that of nitrides and borides. Ti is selected as the two-dimensional MXene 3 C 2 ; Using the Materials Studio software package, the uncomplexed CsPtCl was prepared in a progressive order of (GGA-PBE)-HSE03-HSE06. 3 Band gap calculations yield CsPtCl 3 The band gap is 2.2 eV. Based on this, we selected Ti with excellent conductivity. 3 C 2 ; Ti 3 C 2 Doped CsPtCl 3 Get CsPtCl3 / Ti 3 C 2 Composite materials to achieve the reduction of CsPtCl 3 The purpose of the perovskite band gap.

[0030] CsPtCl 3 Perovskite and Ti 3 C 2 The CsPtCl 3 / MXene theoretical model, when the molar ratio exceeds 1:1, CsPtCl 3 The band gap of perovskite tends to transform into a conductor; within the modification range of 1:50-1:1, if the band gap is higher than 1.5 eV, the doping amount should be further increased; if the band gap is lower than 1.5 eV, the doping amount should be reduced; therefore, adjusting CsPtCl 3 Perovskite and Ti 3 C 2 According to the molar ratio, CsPtCl 3 Perovskite and Ti 3 C 2 CsPtCl was constructed according to the molar ratio of 20:1, 30:1 and 50:1. 3 / MXene theoretical model; CsPtCl 3 Perovskite and Ti 3 C 2 When the molar ratio is 1:1, CsPtCl 3 Perovskite-Ti 3 C 2 -CsPtCl 3 The three-layer sandwich structure of perovskite was modeled and composite material 1 was obtained, where the total energy of composite material 1 is -2.15×10 4 eV; CsPtCl 3 Perovskite and Ti 3 C 2 When the molar ratio is 20:1, CsPtCl 3 Perovskite-Ti 3 C 2 -CsPtCl 3 The three-layer sandwich structure of perovskite was modeled to obtain composite material 2, where the total energy of composite material 2 is -7.08×10 4 eV; CsPtCl 3 Perovskite and Ti 3 C 2When the molar ratio is 30:1, Ti 3 C 2 As the core, CsPtCl 3 Perovskite coated on Ti 3 C 2 Surface, structure CsPtCl 3 / Ti 3 C 2 Composite material, composite material 3 is obtained, where the total energy of composite material 3 is -9.08×10 4 eV; CsPtCl 3 Perovskite and Ti 3 C 2 When the molar ratio is 50:1, Ti 3 C 2 As the core, CsPtCl 3 Perovskite coated on Ti 3 C 2 Surface, structure CsPtCl 3 / Ti 3 C 2 Composite material, composite material 4 is obtained, wherein the total energy of composite material 4 is -1.29×10 5 eV; According to the formula E binding = E CsPtX3 / MXene - E CsPtX3 - E MXene The binding energies of the above composite materials are calculated respectively, among which CsPtCl 3 The total energy of perovskite is -5.68×10 3 eV, Ti 3 C 2 The total energy is -1.02×10 4 eV, the binding energy of composite material 1 is 59.68 eV, the binding energy of composite material 2 is -96.27 eV, the binding energy of composite material 3 is -107.76 eV, and the binding energy of composite material 4 is 231.91 eV; According to the above calculation results and constraints, when the binding energy is less than 0, the structurally stable model is selected, namely composite material 2 and composite material 3; For composite material 2, band gap calculation was performed using Materials Studio, and step-by-step band gap calculations were performed in sequence (GGA-PBE)-HSE03-HSE06 to obtain the band gap calculation results, and the band gap was obtained to be 1.72 eV; For composite material 3, band gap calculation was performed using Materials Studio, and step-by-step band gap calculations were performed in sequence (GGA-PBE)-HSE03-HSE06 to obtain the band gap calculation results, and the band gap was obtained to be 1.61 eV; According to the above calculation results, Ti 3 C 2 With CsPtCl 3 According to the molar ratio of 1: (20~30), CsPtCl 3 / Ti 3 C 2 The band gap of the composite material is closest to 1.5 eV.

[0031] Ti 3 C 2 , CsCl, and chloroplatinic acid were mixed in a molar ratio and prepared in a hydrothermal reactor. The CsPtCl obtained in the test experiment was 3 / Ti 3 C 2 Band gap, compare the material band gap obtained from the experiment with the calculated results, optimize the experimental process, and obtain the band gap value closest to the theoretical calculated results.

[0032] In the above CsPtCl 3 / Ti 3 C 2 Based on the embodiment, referring to the relevant steps, CsPtX with different halogen ions was prepared. 3 Perovskites, including CsPtCl 3 , CsPtBr 3 ,CsPtI 3 , CsPtCl 2 Br, CsPtCl 2 I、CsPtClBrI、CsPtClBr 2 , CsPtClI 2 With a variety of 2D MXene, including Ti 2 C. Ti 2 N.V 2 C、Nb 2 C. Ti 3 C 2 、Ti 3 CN、Nb 4 C 3 、 4 C 3 、Ti 4 N 3 、Mo 2 Ti 2 C 3 Constructed CsPtX 3Related research on / MXene composites has explored the doping ratio closest to the band gap of 1.5eV, which will not be repeated here.

[0033] The method of the present invention constructs CsPtX by Materials Studio software 3 / MXene composite material model, the band gap is calculated according to the progressive order of (GGA-PBE)-HSE03-HSE06, and the appropriate doping ratio is obtained to obtain CsPtX with a stable structure and a band gap of about 1.5eV. 3 / MXene composite materials, thereby reducing the complexity of experimental operations to find suitable band gap materials, shortening the research and development cycle of new materials and saving costs, which has important practical application value.

[0034] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.

Claims

1. A novel perovskite composite material, characterized in that: include: ABX3-type all-inorganic perovskites and two-dimensional MXenes; The molar ratio of the ABX3-type all-inorganic perovskite to the two-dimensional MXene is (1-50):1; In the ABX3 type all-inorganic perovskite, the element replacing the A position is Cs, the transition element replacing the B position is Pt, and the element replacing the X position is a halogen element; The two-dimensional MXene is a transition metal carbide, nitride or boride.

2. The novel perovskite composite material according to claim 1, characterized in that: The halogen elements include Cl, Br, and I, and the element replacing the X position is any combination of one or more of Cl, Br, and I.

3. The novel perovskite composite material according to claim 2, characterized in that: The carbide is one of M2C, M3C2, and M4C3; the nitride includes one of M2N, M3N2, and M4N3; and the boride includes one of M2B2, M3B4, and M4B6.

4. A method for regulating the band gap of a novel perovskite composite material according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1: Using the Materials Studio software package, the band gap of uncompounded CsPtX3 was calculated in the progressive order of (GGA-PBE)-HSE03-HSE06, and conductive two-dimensional MXene and CsPtX3 were selected to construct composite materials; S2: CsPtX3 perovskite and two-dimensional MXene are mixed in molar ratios and the model is constructed using Materials Studio to construct a CsPtX3 / MXene theoretical model. S3: According to the theoretical model of S2, CsPtX3 / MXene composite material is constructed; S4: Establish a theoretical model based on S2, optimize the heterostructure with Materials Studio, and calculate the binding energy of CsPtX3 / MXene composite materials; S5: Select stable CsPtX3 / MXene heterogeneous models and corresponding CsPtX3 / MXene composites according to the constraints; S6: According to the CsPtX3 / MXene composite material in S5, the band gap calculation is performed using Materials Studio, and the step-by-step band gap calculation of (GGA-PBE)-HSE03-HSE06 is performed in sequence to obtain the band gap calculation results; S7: Analyze the band gap calculation results and obtain the material structure and composition of the CsPtX3 / MXene composite material with a band gap of 1.5 eV.

5. The band gap control method of the novel perovskite composite material according to claim 4, characterized in that: In S3, when the molar ratio of CsPtX3 perovskite to two-dimensional MXene is (50-21):1, the two-dimensional MXene is used as the core of the composite material, and the CsPtX3 perovskite is coated on the surface of the two-dimensional MXene to construct the composite material; When the molar ratio of CsPtX3 perovskite and two-dimensional MXene is (20~1):1, a composite material is constructed in the form of a stacked sandwich structure, and a model is established according to the three-layer sandwich structure of CsPtX3 perovskite-two-dimensional MXene-CsPtX3 perovskite.

6. The band gap control method of the novel perovskite composite material according to claim 4, characterized in that: The binding energy of the CsPtX3 / MXene composite material in S4 is E binding = E CsPtX3 / MXene - E CsPtX3 - E MXene ; in, E CsPtX3 / MXene is the total energy of the composite material, E CsPtX3 is the total energy of CsPtX3 perovskite, E MXene is the total energy of the two-dimensional MXene.

7. The band gap control method of the novel perovskite composite material according to claim 4, characterized in that: The constraint condition is that the binding energy of the CsPtX3 / MXene composite material is less than 0.

8. The band gap control method of the novel perovskite composite material according to claim 4, characterized in that: In S2, corresponding CsPtX3 perovskite and two-dimensional MXene theoretical models are constructed according to different molar ratio gradients, and each of the theoretical models is repeated in S3 to S7.

Citation Information

Patent Citations

  • All-inorganic perovskite layer and preparation method and application thereof

    CN110164998A

  • Method for regulating and controlling band gap of organic-inorganic perovskite material

    CN113053467A

  • Preparation method of X-ray detector

    CN114497392A

  • Memristor based on MXene and preparation method thereof

    CN117529221A

  • Two-dimensional perovskite forming material, stacked structure, element, and transistor

    US20180337357A1